Impact of vegetable farming on farmers livelihood patterns in Dhankuta, Nepal - Bhandari, Kishor; Paudel, Basanta (Geographical Journal of Nepal, 2021)
This paper deals with the livelihood pattern and the socio-economic condition of vegetable farmers of Chhathar Jorpati rural municipality, which lies in the eastern part of Dhankuta district of Nepal. The study applied household questionnaire survey, focus group discussion and field observation to collect information of vegetable farming and the impact of vegetable farming on farmers’ livelihood. The study conducted 45 households questionnaire survey in total using simple random sampling in ward number six of Chhathar Jorpati rural municipality. The statistical analysis of collected field survey data was preformed through correlation test and standard deviation. The result shows that the socio-economic condition and the livelihood of the vegetable farmers is improving in recent years. Before doing commercial vegetable farming, farmers cultivated potatoes and used to exchange their production with cereal crops to the neighboring villages. Farmers used to cultivate maize in their farmland, but due to the climatic and the topographic condition it took almost nine months (from January to October) for production. Among the total households, 24.4 percent farmers have seven members in their family and the average family size is 6.3. The Chhetri is the dominant ethnic group of the study area. Among educated groups, the majorities have completed secondary level of education. Most of the farmers are (35.5%) holding land size between 16 and 20 Ropani (0.82-0.10ha.). The majorities of the farmers cultivated high valued vegetables i. e., cauliflower, cabbage, tomato, pea, radish, carrot and green leafy vegetables. The average income from vegetable farming is NRs. 250000/household per year. Primarily, farmers use their income to manage foods, clothes, children education and daily-required goods. Further, due to the lack of sufficient human resources, improved seeds and fertilizer, the majorities of the farmers are facing challenges in their vegetable farming. In addition to this, the vegetable farmers are utilizing their capabilities and are devoted to enhance their livelihood through vegetable farming.